Anomalous electrical conductivity of n-type Te-doped Mg3.2Sb1.5Bi0.5. (December 2017) - Mao, Jun; Wu, Yixuan; Song, Shaowei; Shuai, Jing; Liu, Zihang; Pei, Yanzhong; Ren, Zhifeng
Abstract: Defects, which can scatter the carriers as well as alter the carrier concentration, could greatly impact the material's electrical conductivity. Here we report the anomalous temperature dependences of electrical conductivity observed in n-type Te-doped Mg3 Sb2 -based materials. These anomalies are induced by the variations of Hall carrier concentration and mobility, both of which are influenced by the defects that closely relate to the Te dopant. Our results demonstrate that Te concentration plays a critical role in manipulating the defect chemistry of n-type Mg3 Sb2 -based materials. The intricate relationship among the defects, composition, Fermi level, and temperature significantly complicates our understanding on the thermoelectric properties of n-type Mg3 Sb2 -based materials. Our work indicates that further enhancement in thermoelectric performance of this material is possible if the defects can be effectively controlled. Graphical abstract: Highlights: Anomalous temperature dependence of electrical conductivity is observed in n-type Te-doped Mg3 Sb2 -based materials. The anomalous electrical conductivity can be ascribed to variations in the Hall carrier concentration and mobility. Such variations should be mainly ascribed to the presence of defects which closely depend upon the Te concentration.